Converging worlds of welfare? British and German social policy in the 21st century - Clasen, Jochen (Oxford : Oxford University Press, 2011)
This volume reviews and compares welfare policy change in the UK and Germany. It focuses on family policy, pensions, and the labour market, and covers both public provision as well as the role of company-based social protection.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Public welfare -- Great Britain; Public welfare -- Germany